Mammoth skeleton in Yakutsk, Russia - Campbell, Sady (2014)
Display of a mammoth skeleton (frontal view) at the Mammoth Museum, Severo-Vostochnyy Federal'nyy Universitet Im. M.k. Ammosova, Yakutsk, Sakha Republic, Russia